1992
DOI: 10.1038/nbt0292-176
|View full text |Cite
|
Sign up to set email alerts
|

Growth Enhancement in Transgenic Atlantic Salmon by the Use of an “All Fish” Chimeric Growth Hormone Gene Construct

Abstract: We have developed an "all fish" growth hormone (GH) chimeric gene construct by using an antifreeze protein gene (AFP) promoter from ocean pout linked to a chinook salmon GH cDNA clone. After microinjection into fertilized, nonactivated Atlantic salmon eggs via the micropyle, transgenic Atlantic salmon were generated. The presence of the transgene was detected by polymerase chain reaction (PCR) using specific oligonucleotide primers. A number of these transgenic fish showed dramatic increases in their growth ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
162
0
14

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(179 citation statements)
references
References 20 publications
3
162
0
14
Order By: Relevance
“…The present study showed that the coefficient of variation of final weight was higher in the transgenic carp than in the controls. Large variations in body size or growth in transgenic fish were also reported in other studies (Du et al, 1992;Wei et al, 1992;Devlin et al, 1994). The results suggested that the integration and expression of foreign genes are different in different individuals of the transgenic fish.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The present study showed that the coefficient of variation of final weight was higher in the transgenic carp than in the controls. Large variations in body size or growth in transgenic fish were also reported in other studies (Du et al, 1992;Wei et al, 1992;Devlin et al, 1994). The results suggested that the integration and expression of foreign genes are different in different individuals of the transgenic fish.…”
supporting
confidence: 66%
“…Many investigators reported that the ‡Author to whom correspondence should be addressed. Email: z.zhu@lily.whihb.ac.cn GH-transgenic fish exhibited higher growth rates than the controls (Zhu et al, 1986(Zhu et al, , 1989Chourrout et al, 1986;Dunhan et al, 1987;Rokkones et al, 1989;Zhang et al, 1990;Du et al, 1992). The most dramatic superfish was produced by Devlin et al (1994) who inserted an all-salmon gene construct (pOnMTGH1) into coho salmon Oncorhynchus kisutch (Walbaum).…”
Section: Introductionmentioning
confidence: 99%
“…Stable lines of several species of transgenic fish have been generated, including growth-enhanced 'all-fish' GH transgenic common carp (Cyprinus carpio L.) in China (Wang et al, 2001), growthenhanced transgenic Atlantic salmon (Salmo salar) in Canada (Du et al, 1992;Cook et al, 2000a), growth-enhanced transgenic coho salmon (Oncorhynchus kisutch) in Canada (Devlin et al, 1995), and growth-enhanced transgenic tilapia (Oreochromis sp.) in Britain and Cuba (Rahman et al 1998;Martinez et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The linearized DNA fragment was purified using gel extraction kit (Axygen). After artificial insemination, about 1 nl of linearized recombinant plasmid (100 pg nl À1 ) was microinjected into rare minnow embryo at the 1-2 cell stage under a dissecting microscope with a micromanipulator [28][29][30]. The control group was injected with linearized pCMV-EGFP plasmid.…”
Section: Microinjection and Culture Of Rare Minnow Embryosmentioning
confidence: 99%